Economic Valuation on the Development Plan of the Flower Garden Area using Contingent Valuation Method - Larre, Aura Asyda; Ricardo, Rico; Puspitawati, Eka; Pambudi, Andika (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Non-market value plays a crucial role in the economic valuation of natural resources and the environment. Therefore, this study aimed to estimate the non-market value derived from the development plan of a flower garden area in the Blora Regency. This valuation included individual and aggregate willingness to pay (WTP) and the factors influencing WTP. This study used the Contingent Valuation Method (CVM) as the research approach, with logistic regression as technical analysis. A total of 250 questionnaires were completed by residents of Blora, resulting in a mean value of individual non-market WTP of IDR 10,605 as an entry fee and an aggregate value of IDR 97,567,748/year. The results show that the higher the bid, the lower the probability of paying. Another interesting outcome was that people with an income of over five million and living close tothe garden development plan area had a greater probability of paying than others. These findings provide an overview of the Blora government’s efforts to improve access to areas and facilities within gardens to attract people outside of the characteristics that significantly affect WTP.